Upaya Optimalisasi Pertumbuhan Anak Stunting melalui Peningkatan Pengetahuan Ibu tentang Kesehatan Keluarga - Ulya Uti Fasrini; Desmawati Desmawati; Masrul Masrul; Nur Indrawaty Lipoeto; Delmi Sulastri; Fathiyyatul Khaira; Rahmani Welan; Shinta Ayu Intan; Rinaldiansyah Rinaldiansyah; Muhammad Rayyan Rifqi; Annisaul Husna; Rahmi Nurjannah (Warta Pengabdian Andalas, 2021)
The nutritional problem such as stunting will impact human resource quality. Various factors, including family economic problems, contributed to it, such as in Lambung Bukit Village, Pauh District in Padang City. Apart from financial issues, the mother's lack of illiteracy on child health and nurture also contributes to nutritional problems in this area. Health services that involve physical examinations, child development, nutritional problems and the mother's understanding of family health need to be carried out. Nutrition education was given together with maternal education about parenting and maternal health by the community service team from the Nutrition Science Section and Anatomical Pathology Section, Faculty of Medicine, Andalas University. Thirty mothers accompanied by their toddlers attended the activity. The service team provided five steps that participants must pass, including registration activities, anthropometric examinations, nutritional history, problem assessments, and nutritional consultations. It was hoped that both individual and group approaches would provide significant leverage for changing maternal behaviour. The mother benefited of the education provided. They requested that the team carry out this activity regularly at least once every three months, both to assess the growth and development of children and provide the knowledge about family health they need.